#1**+10 **

First we're going to want to factor these out.

f(x)=x^3+x^2-42x

f(x) = (x)(x^2+x-42) ---this second part can be factored

f(x) = (x)(x+6)(x-7)

Now that this is factored completely, we can find the zeros. The "zeros" of a polynomial funtion like we have here are the numbers you could put in for x to make f(x) = 0.

For instance, if we put in -6 for x, we would get this:

f(x)=(-6)(-6+6)(-6-7)

f(x)=(-6)(0)(-13) ---anything and everything multiplied by zero is zero.

f(x) = 0

Basically you find the opposites of the numbers next to x.

So the zeros are 0, -6, and 7.

NinjaDevo Jun 3, 2015

#1**+10 **

Best Answer

First we're going to want to factor these out.

f(x)=x^3+x^2-42x

f(x) = (x)(x^2+x-42) ---this second part can be factored

f(x) = (x)(x+6)(x-7)

Now that this is factored completely, we can find the zeros. The "zeros" of a polynomial funtion like we have here are the numbers you could put in for x to make f(x) = 0.

For instance, if we put in -6 for x, we would get this:

f(x)=(-6)(-6+6)(-6-7)

f(x)=(-6)(0)(-13) ---anything and everything multiplied by zero is zero.

f(x) = 0

Basically you find the opposites of the numbers next to x.

So the zeros are 0, -6, and 7.

NinjaDevo Jun 3, 2015